Industrial and selectional value of plum Izyum erik (Prunus domestica L.) in the Crimea - Є. П. Шоферістов (Plant Varieties Studying and Protection)
The results of expeditional collections and first varietal study of local varieties of plum Izyum erik have been given in the article. The perspectives of the further use of the studied varieties for selection and testing in industrial conditions, in orchards and plots near the houses have been discussed.